RESISTANCE OF HELMINTH EGGS TO UNFAVORABLE PHYSICAL, CHEMICAL AND BIOLOGICAL FACTORS OF THE ENVIRONMENT. (LITERATURE REVIEW) - D. A. Dolbin; R. Z. Khayrullin (Российский паразитологический журнал, 2019)
Objective of research: The purpose of this paper is the analysis of literature sources on the resistance of some helminth species to unfavorable physical, chemical and biological factors of the environment. Materials and methods: Literature sources that describe the resistance of some species of helminth eggs to unfavorable physical, chemical and biological environmental factors were analyzed. Results and discussion: Nematode eggs ( Parascaris equorum and Ascaris suum) die in water at the temperature of 60 °С for 25-30 sec., at 70-80 °С - for 2 sec.; Ascaridia galli eggs at 45 °С - for 2 hr., at 55 °С - for 2 sec.; Ascaris lumbricoides eggs at 50 °С - for 5 min., at 55-60 °С - for 5 sec. and at 65 °С - for 2 sec. Drying of P. equorum eggs at temperature of 30-36 °С leads to their death after 3-5 days. P. equorum and Ascaris eggs die after 15 min. at temperature of 70 °С. Low air temperatures have different effects on helminth eggs. At temperatures below zero, the metabolic processes and development of P. equorum eggs stop. Concentrated sulfuric, chlorohydric, nitric, carbolic acids as well as creolin, bleach powder, dichloroethane, cresol are mostly used for elimination of helminth eggs. 3 and 5% solutions of disinfectants «Bior-N», «Veltorgan» and «Amocide» can be used for a 100% inhibition of development of ascaris eggs. For the elimination of Ascaris suum eggs, a method of wastewater treatment with the use of phytoplankton Clorella vulgaris and Scenedesmys obliguus has been suggested. Wastewater treated in bioponds is completely cleaned from helminth eggs. Harmful effects of rhizosphere of marigold, pot marigold, barley and millet on helminth eggs were determined. Various protozoa also affect the viability of helminth eggs. So, Amoeba verrucosa can intake ascaris eggs and free larvae released from eggs. Predatory infusoria Bursaria truncatula, Stylonichia mytilus and Stentor sp. intake and ascaris eggs, coracidia of Pseudophyllidea and miracidia of Fasciola hepatica , and completely digest them within 24-72 hrs. Oligochaeta, Bedford’s flatworms (Pseudobiceros bedfordi), aquatic insects, Crustacea and mollusks take part in the elimination of helminth eggs.